An optimum opportunity for interstellar dust measurements by the JUICE mission - Sterken, Veerle Jasmin; Postberg, Frank; Grün, Eberhard (Planetary and space science, 2012)
The JUpiter ICy moons Explorer (JUICE) is an ESA L-class mission concept designed to explore the Galilean satellites of the Jovian system. Although the current mission science goals do not include any astrophysical observations, we find that the planned period of the JUICE mission is optimal for in situ measurements of Interstellar Dust (ISD), due to highly increased flux levels at that time. In case that JUICE carries a dust detector, this could lead to in situ high-resolution mass spectra of ISD grains. Such compositional information on the ISD grains is important for understanding the origins of solar/planetary systems, and therefore could represent a valuable addition to the core JUICE mission science.